John Walley and Jacob Wendell correspondence - Walley, John, 1677-1746.; Wendell, Jacob, 1691-1761.
Letter from Walley and Jacob Wendell, merchants in Boston, Mass., concerning trade in cotton, sugar, and slaves.
Merchant of Boston, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cotton trade; Merchants -- Massachusetts -- Boston; Slave trade; Sugar trade; Boston (Mass.) -- Commerce; Merchants